Constraints faced by the farmers in commercial cultivation of vegetables (Journal of the Bangladesh Agricultural University, 2014)
The study was conducted to determine the constraints faced by the farmers in commercial cultivation of vegetables and to explore relationship between the selected characteristics of the farmers and constraints faced by them. Data were collected through personal interview from 142 randomly selected respondents out of 1422 vegetable growers of the three villages viz. Panchpara, Bagan and Rampur, under Trishal Upazila of Mymensingh district during January to March 2011. In terms of overall constraints the highest portion (83.30%) of the respondents faced medium constraint. Based on constraint facing index (CEI), low price of vegetables during harvesting ranked first followed by lack of quality seed and high wages of labourer. Among the ten selected characteristics, level of education, family size, farm size, extension media contact, knowledge on vegetable production and cosmopoliteness showed significant negative correlation and family subsistence pressure showed significant positive correlation with farmers constraints in commercial cultivation of vegetables. Stepwise multiple regressions showed that extension media contact, cosmopoliteness and knowledge on vegetable production had greater influence on farmers constraints. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19893 J. Bangladesh Agril. Univ. 11(2): 193-198, 2013